PERBEDAAN EFEKTIFITAS MADU DAN SOFRATULLE TERHADAP PENYEMBUHAN LUKA DIABETIK PADA PASIEN DIABETES MELLITUS - Awaluddin Awaluddin; Anita Syarifah; Nurhayatina Nurhayatina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Diabetic wounds are one factor that causes biological, psychological, social, spiritual and economic problems and death due to sepsis. Diabetic wounds easily develop into infections due to the entry of germs or bacteria and the presence of high blood sugar becomes a strategic place for germ growth. The purpose of this study was to analyze the differences in the effectiveness of honey and sofratulle on the diabetic wound healing process of patients with 2nd type of diabetes mellitus in Bhayangkara Hospital Pekanbaru. The research design conducted was pre-experimental research with the design of one group pretest-posttest. The study began on December 17, 2018 - January 17, 2019. The study sample consisted of 20 respondents divided into 2 groups, 10 respondents as the experimental group of wound care with honey and 10 respondents as the experimental group of wound care with sofratulle. The analysis data technique used was independent t-test with a value of α = 0.01. Based on data processing using SPSS obtained p value of 0,000